2020
DOI: 10.1021/acs.molpharmaceut.0c00244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Hexavalent Betulinic Acid Derivative as a Hemagglutinin-Targeted Influenza Virus Entry Inhibitor

Abstract: Naturally occurring pentacyclic triterpenes, such as betulinic acid (BA) and its derivatives, exhibit various pharmaceutical activities and have been the subject of great interest, in particular for their antiviral properties. Here, we found a new anti-influenza virus conjugate, hexakis 6-deoxy-6-[4-N-(3β-hydroxy-lup-20­(29)-en-28-oate)­aminomethyl-1H-1,2,3-triazol-1-yl]-2,3-di-O-acetyl-α-cyclodextrin (CYY1-11, 1), in a mini library of pentacyclic triterpene–cyclodextrin conjugates by performing a cell-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
(106 reference statements)
1
13
0
Order By: Relevance
“…Designed bifunctional amino alkyne linkers of different lengths (1, 2, 4, 6 and 8 OEG units) 26-30 were prepared from commercially available 2-azidoethanol 20, di(ethylene glycol) 8, tetra(ethylene glycol) 9, hexa(ethylene glycol) 10 or octa(ethylene glycol) 11 in 27-64% yields over four steps according to conventional methods (Scheme 1) [30,31]. Compound 31 could be accessed by synthesis from the cheaper precursor betulin, as reported previously [25,32]. Subsequent activation of the carboxylic acid by using TBTU/DIPEA in THF gave compound 32 in 83% yield, which was then subjected to aminolysis with commercially available propargylamine or bifunctional aminoalkyne linkers 26-30 to afford BA derivatives 33-38 bearing a terminal alkynyl group at the C-28 position (Scheme 2), and their structures were characterized with 1 H and 13 C NMR (Supplementary Materials).…”
Section: Synthesis Of Ba-based Alkynes 33-38mentioning
confidence: 99%
See 3 more Smart Citations
“…Designed bifunctional amino alkyne linkers of different lengths (1, 2, 4, 6 and 8 OEG units) 26-30 were prepared from commercially available 2-azidoethanol 20, di(ethylene glycol) 8, tetra(ethylene glycol) 9, hexa(ethylene glycol) 10 or octa(ethylene glycol) 11 in 27-64% yields over four steps according to conventional methods (Scheme 1) [30,31]. Compound 31 could be accessed by synthesis from the cheaper precursor betulin, as reported previously [25,32]. Subsequent activation of the carboxylic acid by using TBTU/DIPEA in THF gave compound 32 in 83% yield, which was then subjected to aminolysis with commercially available propargylamine or bifunctional aminoalkyne linkers 26-30 to afford BA derivatives 33-38 bearing a terminal alkynyl group at the C-28 position (Scheme 2), and their structures were characterized with 1 H and 13 C NMR (Supplementary Materials).…”
Section: Synthesis Of Ba-based Alkynes 33-38mentioning
confidence: 99%
“…In addition, the CC 50 was not determined for 51 because the dose-response curve was not achieved at the highest concentration tested (200 µM), displaying over 38.4-fold selectivity. Detailed studies on the biological activities of 51 have been described by Chen et al [25]. The CC 50 values of conjugates 69-71 in MDCK cell were also not determined because they had a value over 100 µM, in other words they were also not cytotoxic.…”
Section: Anti-influenza A/wsn/33 Virus Activity Of Multivalent Ba-cd ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Betulinic acid is one of the main effective ingredients of JF. Studies have shown that it has therapeutic effects on various diseases, such as influenza virus infection, 82 glioblastoma, 83 ischemic stroke, 84 and a variety of malignant tumors. 85,86 In addition, betulinic acid has unique effects on improving AD and combating anxiety/depression.…”
mentioning
confidence: 99%